Exploring Sources of Errors in L3 English Production of Natives of Moroccan Arabic - Oubadi, Youssef (International Journal of Language and Literary Studies, 2024)
Language learners’ writing products can provide insights into how these learners acquire the target language through the analysis of the committed errors. Indeed, research has revealed that error analysis in writing essays is crucial for understanding and improving language acquisition by identifying common errors, and their sources, and informing teaching strategies to address these issues. The current paper aims to identify, describe and analyze errors committed by Moroccan secondary school students in writing. The study also attempts to determine some of the possible causes of the errors to offer an understanding of how linguistic interference influences the foreign language learning process. To this end, a sample of tasks written in English by a group of 20 secondary school students was collected. Then, an analysis procedure was conducted to analyze errors and explain their sources. Hence, this study adopts a mixed-method approach design to generate qualitative as well as quantitative data by identifying error categories and calculating the total number of error types and sources, respectively. The findings show that the errors are committed both at the word as well as the sentential level including lexical, grammatical, substance, and syntactic errors. Besides, the results indicate that learners commit errors in their English writings partly due to interference of Moroccan or Standard Arabic and French, but mostly due to other developmental sources within the scope of the target language. These findings offer valuable insights into how learners acquire a second or foreign language and what obstacles they encounter in the learning process and, thus, could suggest some implications to reduce the errors caused by negative language transfer and improve learners’ language proficiency.